2010
DOI: 10.1254/jphs.10r02fm
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Research on Dopamine Signaling to Develop Drugs for the Treatment of Mental Disorders: Proteins Interacting With the Third Cytoplasmic Loop of Dopamine D2 and D3 Receptors

Abstract: Abstract. Among the various dopamine receptors, D 2 -like receptors (D2R, D3R, and D4R) are characterized by a large third cytoplasmic loop, a short carboxyl-terminal tail, and the ability to activate inhibitory G proteins. The diverse activities of D 2 -like receptors are partly mediated by proteins that interact with the third cytoplasmic loop, which regulate receptor signaling, receptor trafficking, and stability. Furthermore, in the case of D2R and D3R genes, mRNA splicing generates isoforms in the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The finding that the majority of brain D 2 R is expressed DRM fractions has exposed a major limitation of common approaches for identifying components of the D 2 R signaling complex in the brain. Due to the physiological and clinical importance of D 2 R, a large amount of such effort has been invested in identifying the different protein interactions that comprise the D 2 R ‘signalplex’ (Kabbani and Levenson 2007; Shioda et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the majority of brain D 2 R is expressed DRM fractions has exposed a major limitation of common approaches for identifying components of the D 2 R signaling complex in the brain. Due to the physiological and clinical importance of D 2 R, a large amount of such effort has been invested in identifying the different protein interactions that comprise the D 2 R ‘signalplex’ (Kabbani and Levenson 2007; Shioda et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of D2R interacting proteins, using yeast two-hybrid, co-immunoprecipitation, glutathione S-transferase (GST) pull-down and in vitro binding assays, have identified about 20 proteins with many of them relevant to schizophrenia (Wang et al, 2008 ; Shioda et al, 2010 ; Kabbani et al, 2012 ). These proteins selectively regulate specific signaling pathways and function of D2R via protein-protein interactions, without affecting other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that some FABPs, such as H-FABP or B-FABP, could interact with membrane-associated receptors, including integrin or dopamine D2 receptor [ 9 11 ], and that L-FABP may associate with cell membranes or membrane proteins [ 5 , 12 ]. A recent study also revealed that L-FABP was significantly associated with hepatocyte plasma membrane cholesterol-rich microdomains [ 13 ].…”
Section: Resultsmentioning
confidence: 99%